A review of evidence-based clinical practice on fascia iliaca compartment block for lower limb injury. (September 2021) - Tarekegn, Fantahun; Sisay, Amanuel
Abstract: Background: The main objective of this study was to resolve fascia iliaca compartment block controversies by putting the currently available evidences applied for knee, femoral shaft, and hip bone injury or related to surgery. Methods: The databases PubMed, Cochrane Review, and Google Scholar were searched without regard to language or publication type for fascia iliaca compartment block before December 2020. After eligibility sorting and duplicate removal, a total of 26, 609 articles were identified, with 21 of them being included for review. Discussion: In the emergency department, fascia iliaca compartment block (FICB) has now become the standard of practice. Various evidence suggested that 20–40 ml of local anesthetic was required for an effective block in adult patients. Conclusion: For the knee, femoral bone, and hip region surgery, the fascia iliaca compartment block (FICB) provided better anesthesia quality, reduced systemic morphine consumption, and had fewer complications than epidural anesthesia. Anesthetists and surgical department staff should promote the FICB's benefits by emphasizing its superiority in pain management. Highlights: The fascia iliaca compartment block is a triangular space In the emergency department, fascia iliaca compartment block has now become the standard of practice. The fascia iliaca compartment block (FICB) was found to have a higher rate of success than the 3 in 1 block in both children and adults. The femoral, lateral cutaneous nerve of the thigh, and obturator nerves are paralyzed by fascia iliaca compartment block